Irina Yányshev Nésterova. Canarias en las relaciones hispano-soviéticas, 1965-1991. Las Palmas de Gran Canaria, Ediciones Idea, 2019, 471 pp. ISBN: 8417764356. - Matés Barco, Juan Manuel (Investigaciones de Historia Económica, 2021)
Sin resumen